Feeding and arrestment responses of Diabrotica speciosa to cucurbitacin-content formulations - Arruda, Iara Cintra (2005)
The objective of this work was to evaluate arrestant and stimulant feeding effects on Diabrotica speciosa (Ger.), using cucurbitacin-content starch-based formulations prepared with varying starch sources, and adding potassium lignate. In a glass slide assay, the wash off resistance of formulations was compared. Potassium lignate did not improve wash off resistance. Lagenaria vulgaris L. powder, in which cucurbitacin B concentration was determined as 0.28%, was added to the most adhesive formulation. The resultant material was used in a two-choice assay in which leaves of common bean, Phaseolus vulgaris L., treated with concentrations of 2.5%, 5%, 10%, 15% and 20% were offered to insects together with untreated control leaves. Greater number of insects and leaves consumed were found on leaves treated with cucurbitacin-content formulation (2.5%, 5% – greatest response –, 10% and 15% concentrations) than on untreated control leaves. The concentration, in which responses were higher, was sprayed in a bean field at 1,000, 1,900 and 3,000 g ha-1. Greater number of beetles was found in plots treated with the highest dosage, 3 and 6 days after spraying. Ten days after spraying, no significant differences were found among dosages, probably due to washoff of the bait.